Lithium ion secondary battery without diaphragm or with diaphragm and manufacturing method thereof

By introducing specific unsaturated borate monomers into the polymer matrix and polymerizing in situ, borate ester-based polymers are formed, which solves the problem of low ion conduction capacity of the polymer solid electrolyte at room temperature, and improves the cycle stability and battery capacity of the lithium-ion secondary battery.

CN119920947APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411423851.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The low ion conduction capability of polymer solid electrolytes at room temperature limits its application in lithium-ion batteries, and traditional modification methods have safety hazards and high cost problems.

Method used

By introducing specific unsaturated borate monomers into the polymer matrix and performing in-situ polymerization, borate ester-based polymers are formed, thereby improving the ionic conductivity and lithium ion migration number of the electrolyte.

Benefits of technology

The cycle stability and battery capacity of lithium-ion secondary batteries are improved, and compatibility and processability problems are solved, achieving higher safety and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081603010000031
    Figure BDA0005081603010000031
  • Figure BDA0005081603010000032
    Figure BDA0005081603010000032
  • Figure BDA0005081603010000071
    Figure BDA0005081603010000071
Patent Text Reader

Abstract

The invention relates to a lithium ion secondary battery and a manufacturing method thereof. The lithium ion secondary battery comprises a positive electrode, a negative electrode and a polymer solid electrolyte, wherein the polymer solid electrolyte comprises a borate polymer as a component (A), a polymer matrix as a component (B) and a lithium salt as a component (C); the boric acid ester polymer comprises a specific unsaturated boric acid ester monomer structural unit; and the borate polymer is polymerized in situ in the polymer solid electrolyte. According to the invention, a boric acid ester functional group is introduced into the polymer solid electrolyte and has a synergistic effect with an existing functional group in a polymer matrix, and meanwhile, migration of anions can be inhibited, so that the ionic conductivity and the ionic transference number of the polymer solid electrolyte can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium ion secondary battery and a manufacturing method thereof, belonging to the technical field of lithium ion batteries. Background Art

[0002] With the growing demand for energy in the consumer electronics and electric vehicle markets, it is urgent to develop sustainable energy storage devices with high energy density and high safety. Among all energy storage devices, lithium batteries have been widely studied due to their excellent reversible capacity. However, the liquid electrolyte used in traditional lithium batteries has serious side reactions with the electrodes, resulting in low capacity and poor cycle stability. In addition, liquid electrolytes have risks such as leakage and poor safety performance.

[0003] Solid polymer electrolytes are considered to be the most promising candidate materials for achieving high specific energy density in high-voltage lithium batteries due to their flexibility, ease of preparation, low cost, and good safety. Common polymers such as PVDF and PEO as solid electrolyte substrates have high crystallinity and high glass transition temperature at room temperature, low ionic conductivity, and may also have problems such as low mechanical strength and poor thermal stability, which hinder their practical application.

[0004] At the same time, in polymer solid electrolytes, due to the high coupling between cations and Lewis base sites in the polymer matrix, the lithium ion migration number is generally less than 0.5, that is, the lithium conductivity of polymer solid electrolytes is poor.

[0005] In order to improve the ionic conductivity of solid polymer electrolytes, they can usually be modified by introducing plasticizers or inorganic fillers, blending, grafting, copolymerization, etc.

[0006] Some documents disclose a lithium borate solid electrolyte and its application. The lithium borate solid electrolyte uses a lithium borate with a tetrahedral lithium boron oxygen structure as the center and mainly a flexible ether oxygen chain segment as the side chain as the main component. + On the basis of the low crystallinity and high dissociation degree, high ionic conductivity and cation transfer number are obtained. However, with the development of lithium-ion batteries, it cannot be said that the lithium borate solid electrolyte has achieved sufficient ionic conductivity.

[0007] It can be seen that although a series of studies have been conducted in this field on the improvement of polymer solid electrolytes, there is still room for further improvement in the development of polymer solid electrolytes with high ionic conductivity. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] As mentioned above, polymer solid electrolytes have advantages such as good safety, however, their low ion conductivity at room temperature limits the development of polymer solid electrolytes. In order to enhance the room temperature ionic conductivity of polymer solid electrolytes, researchers have proposed methods such as introducing plasticizers, inorganic fillers, polymer blending, and copolymerization.

[0010] The introduction of plasticizers with high dielectric constants can promote the dissociation of lithium salts. However, the introduction of plasticizers not only affects the thermal stability of polymer electrolytes, but also reduces the mechanical strength of polymer electrolyte membranes, and still poses a safety hazard. Inorganic fillers are prone to agglomeration in polymers, which in turn affects the lithium ion transmission channel. It is often necessary to introduce a large amount of organic solvents to make them evenly dispersed. However, the solvents are difficult to completely remove during the subsequent drying process, which will lead to a series of problems such as increased interface impedance, reduced cycle life, and poor safety during battery cycling.

[0011] However, methods such as blending and copolymerization in the prior art usually require the addition of multiple small molecules for polymerization in order to achieve the purpose of simultaneously improving ionic conductivity, mechanical strength and thermal stability. However, the addition of multiple small molecule monomers will make the structure and degree of polymerization after polymerization, the repeatability of the experiment, etc. more difficult to control and the cost is high.

[0012] Furthermore, as a previous research result of the applicant, in the Chinese patent application with application number 202410670877.5, in-situ polymerization was used to improve the performance of the final electrolyte. Although this achievement has aroused some interest in the subsequent in-situ polymerization modification route of the applicant, however, in the subsequent specific practice, it was also found that even if the in-situ polymerization method is adopted, the result is strongly dependent on the type of monomer. This is mainly due to the differences in compatibility, flexibility / crystallization, ion coordination, electrochemical window performance, voltage resistance / heat resistance, etc. between different monomers and their polymers. For example, many polar monomers are not suitable for this polymerization route, resulting in phase separation after in-situ polymerization, or the product of in-situ polymerization cannot achieve the required ion conductivity, stability and other requirements in electrical testing. Therefore, for the desired performance improvement, the type of monomer still needs to be selected very carefully.

[0013] In order to solve the above problems, based on further research, the present invention provides a lithium-ion secondary battery, which includes a positive electrode, a negative electrode and a polymer solid electrolyte, wherein the polymer solid electrolyte contains: a borate polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C); wherein the borate polymer includes a structural unit of a specific unsaturated borate monomer.

[0014] The polymer solid electrolyte contains borate polymers formed by in-situ polymerization, and introduces a structural unit of a specific unsaturated borate monomer in a polymer material (such as PVDF, PEO, PMMA, PAN, etc.). By introducing a borate group that can interact with the anion part in the lithium salt into the polymer solid electrolyte, the polymer solid electrolyte of the specific structure improves the ionic conductivity of the polymer solid electrolyte, and also improves the lithium ion migration number of the electrolyte, and does not have problems in compatibility and processability. Thus, the cycle stability of the lithium ion secondary battery is improved, and its battery capacity is high.

[0015] Furthermore, the present invention also provides a method for manufacturing a lithium ion secondary battery. By means of the manufacturing method, a lithium ion secondary battery having improved cycle stability and high battery capacity is provided.

[0016] Solutions for solving problems

[0017] In view of such circumstances, the present inventors have diligently studied and provided the following embodiments.

[0018] One aspect of the present invention provides a diaphragm-free lithium-ion secondary battery, which is a diaphragm-free lithium-ion secondary battery comprising a positive electrode, a negative electrode and a polymer solid electrolyte, characterized in that:

[0019] The polymer solid electrolyte comprises: a borate polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C);

[0020] Wherein, the borate polymer comprises a structural unit derived from an unsaturated borate monomer represented by formula (1);

[0021]

[0022] in,

[0023] R1 to R3 are the same or different; and R1 to R3 are independently selected from monovalent organic groups, or R1 and R2 as organic groups can be connected to form a ring by bonding; at least one of R1 to R3 or the cyclic structure formed by R1 and R2 has an unsaturated structure;

[0024] n represents 0 or 1,

[0025] The borate ester polymer is in-situ polymerized in the polymer solid electrolyte.

[0026] Another aspect of the present invention provides a diaphragm lithium ion secondary battery, which is a diaphragm lithium ion secondary battery comprising a positive electrode, a negative electrode, a diaphragm and a polymer solid electrolyte, characterized in that:

[0027] The polymer solid electrolyte comprises: a borate polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C);

[0028] Wherein, the borate polymer comprises a structural unit derived from an unsaturated borate monomer represented by formula (1);

[0029]

[0030] in,

[0031] R1 to R3 are the same or different; and R1 to R3 are independently selected from monovalent organic groups, or R1 and R2 as organic groups can be linked to form a ring by bonding; at least one of R1 to R3 or the cyclic structure formed by R1 and R2 has an unsaturated structure;

[0032] n represents 0 or 1,

[0033] The borate ester polymer is in-situ polymerized in the polymer solid electrolyte.

[0034] Further, according to the above-mentioned lithium ion secondary battery, it is characterized in that the unsaturated borate monomer has 1 to 3 unsaturated groups;

[0035] Preferably, the unsaturated group is selected from alkenyl groups; more preferably, the unsaturated group is selected from alkenyl groups having 2 to 4 carbon atoms.

[0036] Furthermore, according to the above lithium ion secondary battery, it is characterized in that n=1, and R1 to R3 are independently selected from substituted or unsubstituted hydrocarbon groups having 1 to 20 carbon atoms.

[0037] Furthermore, according to the above-mentioned lithium ion secondary battery, it is characterized in that n=0, R1 to R3 are independently selected from substituted or unsubstituted hydrocarbon groups having 1 to 20 carbon atoms, and R1 and R2 are connected to each other to form a ring or are independent of each other.

[0038] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the R1 to R3 are independently selected from linear, branched, aliphatic or aromatic hydrocarbon groups having 2 to 10 carbon atoms, and the hydrocarbon groups may optionally have substituents.

[0039] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the unsaturated borate monomer represented by formula (1) comprises at least one selected from the following:

[0040] Triallyl borate, allyl borate pinacol ester, trans-crotonyl borate pinacol ester, (3-buten-1-yl) borate pinacol ester, 3-methyl-2-butenyl borate pinacol ester.

[0041] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the mass ratio of the monomer amount of the component (A) to the amount of the component (B) is 1:10 to 10:1.

[0042] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the component (A) and the component (B) in the polymer solid electrolyte form an interpenetrating network structure in molecular structure.

[0043] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the polymer solid electrolyte is an all-solid electrolyte.

[0044] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the polymer matrix is ​​selected from at least one of PVDF, PVDF-HFP, PEO and PAN.

[0045] In the present invention, according to the above-mentioned lithium ion secondary battery, it is characterized in that the mass content of the lithium salt in the polymer solid electrolyte is 10% to 60%.

[0046] Another aspect of the present invention provides a method for manufacturing the lithium-ion secondary battery according to the above, characterized in that it comprises the following steps:

[0047] The polymer matrix, lithium salt, unsaturated borate monomer and initiator are mixed in an organic solvent to obtain a mixed solution;

[0048] The unsaturated borate monomer is polymerized to obtain the polymer solid electrolyte.

[0049] Effects of the Invention

[0050] The lithium ion secondary battery of the present invention uses a polymer solid electrolyte introduced with a polyborate material, so that the cycle stability and life of the lithium ion secondary battery are further improved, and the battery capacity is high. Specifically,

[0051] 1) The introduced polyborate materials, whose "borate" functional groups have a synergistic effect with the existing functional groups in the polymer matrix, can effectively improve the ionic conductivity of the polymer solid electrolyte;

[0052] 2) By adding small molecule monomers of unsaturated borate esters to the polymer matrix solution, and then fully stirring and directly polymerizing in situ in the solution, the composite polymer material obtained by this method has good compatibility, and the two polymer molecular chains are fully compatible and entangled. This can inhibit the crystallinity of the polymer matrix at room temperature, enhance the movement of the chain segments, and further improve the lithium ion transmission capacity.

[0053] 3) If the added ester monomer has multiple double bonds, it will be conducive to the formation of a cross-linked structure, promoting the formation of an interpenetrating network structure between the polymer matrix material and the polymer chain formed by in-situ polymerization, thereby further inhibiting the crystallization ability of the polymer molecular chain and improving the lithium ion transmission capacity.

[0054] 4) After polymerization, the polymer solid electrolyte contains "borate" groups as a whole, which can form a coupling with the anion part of the lithium salt, thereby inhibiting the migration of anions and improving the migration ability of lithium ions. DETAILED DESCRIPTION

[0055] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0056] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0057] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0058] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0059] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0060] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0061] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".

[0062] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0063] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.

[0064] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.

[0065] The present invention mainly provides a lithium ion secondary battery, which comprises a polymer solid electrolyte modified by in-situ polymerization. By introducing a small molecule unsaturated borate monomer into a traditional polymer matrix material and performing in-situ polymerization to modify the polymer matrix material, the ion conductivity of the polymer solid electrolyte is improved, thereby improving the cycle stability and battery capacity of the lithium ion secondary battery.

[0066] The present invention is mainly obtained through the following insights:

[0067] As mentioned above, the previous methods of forming polymer electrolytes by blending and copolymerization modification have many shortcomings.

[0068] Through the research of the present invention, it has been found that by introducing unsaturated borate monomers with specific structures into traditional polymer matrix materials and modifying the polymer matrix materials by in-situ polymerization, the problems of existing modified polymer solid electrolytes can be solved and the problems of traditional polymer matrix material applications can be overcome.

[0069] The present invention has found that in the preparation of polymer solid electrolytes, the adverse effects caused by interface compatibility have a great impact on the electrochemical stability of polymer solid electrolytes. Therefore, the present invention introduces small molecule monomers into the polymer matrix solution and directly performs in-situ polymerization in the solution, so that the two polymer molecular chains can be fully compatible, entangled, and form an interpenetrating network structure, thereby effectively improving the interface compatibility of each component in the polymer solid electrolyte. In addition, the interpenetrating network can also inhibit the crystallinity of the polymer matrix at room temperature, enhance the movement of chain segments, and further improve the transmission capacity of lithium ions.

[0070] Therefore, the prepared polymer solid electrolyte membrane can not only improve the lithium ion transportability, but also broaden the electrochemical window to match high voltage, and can also effectively improve the battery's cycle stability and battery capacity.

[0071] <First aspect>

[0072] The first aspect of the present invention provides a membrane-less lithium-ion secondary battery, which is a membrane-less lithium-ion secondary battery comprising a positive electrode, a negative electrode and a polymer solid electrolyte, wherein the polymer solid electrolyte comprises: a borate polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C).

[0073] Optionally, the first aspect of the present invention provides a lithium-ion secondary battery with a separator, which is a lithium-ion secondary battery with a separator comprising a positive electrode, a negative electrode, a separator and a polymer solid electrolyte, wherein the polymer solid electrolyte is the same as the above-mentioned polymer solid electrolyte, that is, the polymer solid electrolyte comprises: a borate polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C).

[0074] In addition, the polymer solid electrolyte composition may further include various functional additive components without hindering the realization of the technical effects of the present invention.

[0075] In some specific embodiments, preferably, the lithium secondary battery can be an all-solid-state battery, which is allowed to not contain liquid electrolyte and separator, and relies on solid electrolyte to isolate the positive and negative electrodes and transmit lithium ions.

[0076] In a preferred embodiment, the lithium ion secondary battery of the present invention is a diaphragm-free lithium ion secondary battery, in which the polymer solid electrolyte also has the function of a diaphragm that isolates the positive and negative electrodes.

[0077] For the positive electrode in the lithium secondary battery, a high-voltage oxide positive electrode material used in lithium-ion batteries can be used, such as lithium cobalt oxide (LCO), lithium nickel manganese oxide (LNMO), and high-nickel content ternary positive electrode (6 series, 8 series) materials (such as NCM811, NCA622, etc.).

[0078] In some specific embodiments, there is no particular limitation on the negative electrode, which can be a common negative electrode for solid polymer batteries. Preferably, the negative electrode is a lithium negative electrode.

[0079] In some specific embodiments, the separator is not particularly limited and may be a separator commonly used in lithium-ion secondary batteries.

[0080] Component (A)

[0081] The borate polymer as component (A) described in the present invention is derived from a small molecular unsaturated borate monomer, and the borate polymer is in situ polymerized in the polymer solid electrolyte. In some specific embodiments, the unsaturated borate monomer used in the present invention has a structure shown in the above formula (1).

[0082]

[0083] Among them, R1~R3 ​​are the same or different; and R1~R3 ​​are independently selected from monovalent organic groups, or R1 and R2 as organic groups can be connected to form a ring through bonding; R1~R3 ​​or at least one of the cyclic structures formed by R1 and R2 has an unsaturated structure; n represents 0 or 1.

[0084] For the above-mentioned monovalent group, in some specific embodiments, it can be a substituted or unsubstituted hydrocarbon group with 1 to 20 carbon atoms, preferably 2 to 10 carbon atoms. Such hydrocarbon groups can be straight-chain, branched, aliphatic or aromatic ring hydrocarbon groups. In addition, there is no particular limitation on the substituents of the hydrocarbon groups in principle, for example, they can be halogen-containing groups, such as F atoms, etc. Typically, such hydrocarbon groups can be methyl, ethyl, propyl, butyl, unsaturated straight-chain or branched olefins with 2 to 8 carbon atoms, phenyl, etc.

[0085] In some specific embodiments, the unsaturated borate monomer has 1 to 3 unsaturated groups. In a preferred embodiment, the unsaturated group is selected from an alkenyl group, and further preferably, the unsaturated group is selected from an alkenyl group having 2 to 4 carbon atoms. For such a group, it is preferably a double bond that can be polymerized by free radicals. When the added ester monomer has multiple double bonds, it is beneficial to form a cross-linked structure in the polymer matrix material, promote the formation of an interpenetrating network structure between the polymer matrix material and the polymer chain formed by in-situ polymerization, thereby further inhibiting the crystallization ability of the polymer molecular chain and improving the lithium ion transmission capacity.

[0086] In some preferred embodiments, n=1, and R1-R3 are independently selected from substituted or unsubstituted hydrocarbon groups with carbon atoms of 1 to 20. In some preferred embodiments, n=0, R1-R3 are independently selected from substituted or unsubstituted hydrocarbon groups with carbon atoms of 1 to 20, and R1 and R2 are connected to form a ring or are independent of each other.

[0087] In a preferred embodiment, the unsaturated borate monomer represented by formula (1) comprises at least one selected from the following: triallyl borate, allyl borate pinacol ester, trans-crotonyl borate pinacol ester, (3-butene-1-yl) borate pinacol ester, 3-methyl-2-butenyl borate pinacol ester.

[0088] In some specific embodiments, unsaturated borate monomers are in situ polymerized through unsaturated carbon-carbon double bonds to form borate polymers, which are fully compatible with the polymer matrix material and form molecular chain entanglement, disrupting the orderly arrangement of the polymer matrix molecules, inhibiting its crystallinity at room temperature, enhancing chain segment movement, and improving the lithium ion transmission capacity.

[0089] As for the unsaturated borate ester monomer of the present invention, only one kind may be used, or two or more kinds may be used simultaneously when necessary.

[0090] In addition, in addition to the above-mentioned unsaturated borate monomers, other unsaturated monomers can also be used in component (A) of the present invention. When other unsaturated monomers are used, these monomers account for less than 10% by mass of the total mass of all monomers, preferably less than 8% by mass, and more preferably less than 5% by mass.

[0091] Component (B)

[0092] The polymer matrix as component (B) in the present invention is provided as a base material.

[0093] The type of polymer matrix may be a high molecular polymer material. These polymer materials generally have a higher dielectric constant, which can make the lithium salt described below more ionized. In addition, the polymer matrix needs to have a lower glass transition temperature to promote the movement of molecular chains at room temperature.

[0094] In some specific embodiments of the present invention, such a polymer matrix can be selected from one or a combination of two or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), polyethylene oxide (PEO), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer (PVDF-TrFE-CTFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyurethane (PU), polyurea (PUA), polyvinyl pyrrolidone (PVP), polyvinyl chloride (PVC), polypropylene carbonate (PPC), polyimide, nylon, polyethylene terephthalate, poly-2-vinyl pyridine, poly-4-vinyl pyridine, etc. More preferably, the polymer matrix is ​​at least one selected from PVDF, PVDF-HFP, PEO, and PAN.

[0095] In some preferred embodiments, the borate polymer is in situ polymerized in the polymer solid electrolyte, thereby forming an interpenetrating network structure between the component (A) and the component (B) in the polymer solid electrolyte in terms of molecular structure.

[0096] In some preferred embodiments, the polymer matrix may include a fluorine-containing polymer, which may further promote the compatibility and synergistic effect between the polymer matrix and the borate ester polymer.

[0097] Component (C)

[0098] The lithium salt as component (C) described in the present invention is the source of active ions in the polymer solid electrolyte and is included in the polymer solid electrolyte system. Without the lithium salt, the polymer solid electrolyte will lose the function of conducting active ions and the entire battery will not work.

[0099] In some specific embodiments, the lithium salt can be selected from one or more of the salts formed by lithium ions and the following anions: PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、N(FSO2)2 - 、C(CF2SO2)3 - 、C2BF2O4 - wait.

[0100] In some preferred embodiments, the lithium salt may be selected from one or a combination of two or more of lithium hexafluorophosphate (LiPF6) or lithium bis(fluorosulfonyl)imide (LiFSI).

[0101] Composition of polymer solid electrolyte

[0102] Regarding the composition of the polymer solid electrolyte of the present invention, from the aspect of improving the electrical properties of the electrolyte, the content of each component of the present invention can be arranged as follows:

[0103] The mass ratio of component (A) to component (B) is 1:10 to 10:1, preferably 1:5 to 5:1, such as 1:8, 1:6, 1:4, 1:3, 8:1, 6:1, 4:1, 3:1, etc. If the content of component (A) is too low, the corresponding effects of inhibiting crystallization, sufficient cross-linking, and strong interaction between functional groups will not be achieved; if the content of component (A) is too high, the mechanical properties of the polymer film are poor, and even film formation is impossible.

[0104] The content of component (C) is not particularly limited in principle, and can be selected in accordance with the general specifications of the amount of lithium salt used in the art. In some specific embodiments, the content of component (C) is 10% to 80% by weight of the sum of the weight of component (A) and component (B), preferably 20% to 40% by weight, such as 20%, 30%, 40%, 50%, 60%, 70%, etc. If the content of component (C) is too low, the lithium ion transmission capacity will be reduced; if the content of component (C) is too high, it will lead to an unnecessary increase in cost and may also affect the mechanical properties of the polymer solid electrolyte.

[0105] In some specific embodiments, the mass content of the lithium salt as component (C) in the final polymer solid electrolyte is 10% to 60%, preferably 20% to 40%. When the content of the lithium salt is within the above range, the lithium ion transport capacity of the polymer solid electrolyte is favorable.

[0106] In some specific embodiments, a certain amount of polymer matrix, such as PVDF, PVDF-HFP, PEO, PAN, etc., is dissolved in an organic solvent in a reactor, a certain amount of lithium salt is added and stirred until dissolved (lithium salt acts as a "solute" to dissociate lithium ions in the lithium salt, and then the migration of lithium ions can be achieved, otherwise it cannot become an electrolyte, just like a liquid electrolyte, a solvent is required. Like lithium salt, lithium salt is first dissociated in the liquid electrolyte and then can be transported in the solvent), and then added A certain amount of unsaturated borate monomer (e.g., allyl boric acid pinacol ester) is added, and then a certain amount of thermal initiator (e.g., azobisisobutyronitrile) is added, and an inert gas (e.g., argon) is introduced into the solution to expel the air dissolved in the solvent and in the conical flask, and then the conical flask is sealed, stirred in an oil bath for a period of time, and then heated to a certain temperature to decompose the initiator (if the initiator is perazobisisobutyronitrile, the temperature is raised to 60-80° C.), stirred vigorously at this temperature for a period of time (e.g., 12 hours), and then cooled to room temperature to take out the solution, and cast the film. Afterwards, the used solvent is removed by any solvent removal method.

[0107] The (usage) form of polymer solid electrolyte

[0108] Regarding the form of the polymer solid electrolyte of the present invention, in some specific embodiments, the polymer solid electrolyte composition can be provided separately, and in other specific embodiments, it can be provided integrally with a separator.

[0109] In some specific embodiments, the polymer solid electrolyte obtained by the present invention substantially does not contain organic solvents or (at room temperature) liquid electrolytes. Preferably, the polymer solid electrolyte of the present invention is a fully solid electrolyte.

[0110] <Second Aspect>

[0111] A second aspect of the present invention provides a method for manufacturing the lithium ion secondary battery of the first aspect, wherein the method comprises the following steps:

[0112] The polymer matrix, lithium salt, unsaturated borate monomer and initiator are mixed in an organic solvent to obtain a mixed solution;

[0113] The unsaturated borate monomer is polymerized to obtain the polymer solid electrolyte.

[0114] The types and amounts of the polymer matrix, lithium salt, and unsaturated borate monomer are the same as those in the first aspect and will not be described in detail herein. They can be appropriately selected and adjusted according to the intended use.

[0115] The initiator described in the present invention may be a free radical initiator, which is used to cause the unsaturated borate ester monomer to undergo free radical polymerization in the polymer matrix to form a cross-linked network.

[0116] In some specific embodiments, the free radical initiator can be a thermal initiator or a photoinitiator, which can be appropriately selected according to the intended use.

[0117] The type of thermal initiator may be one or two or more selected from azo initiators, organic peroxide initiators and the like.

[0118] In some specific embodiments, the thermal initiator may include one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, dibenzoyl peroxide, diethylhexyl peroxydicarbonate, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxydicarbonate, potassium persulfate or ammonium persulfate.

[0119] In some specific embodiments, the photoinitiator can be selected from one or more of cleavage-type initiators such as benzoin and its derivatives, acetophenones, aromatic ketones and acylphosphine oxides; or, it can be selected from one or more of hydrogen-abstraction-type initiators such as benzophenones, thioxanthones, camphor porquinone and bisimidazole.

[0120] Regarding the amount of initiator added, according to the polymerization reaction, it is necessary to carry out sufficient polymerization under relatively strict experimental conditions, but the polymerization method in the present invention cannot guarantee the experimental conditions. Therefore, in order to avoid the termination of the polymerization reaction due to side reactions such as chain transfer in the early stage of decomposition of the initiator, more active free radicals are required, so the initiator ratio should not be too low.

[0121] In some specific embodiments, the amount of initiator added is 0.01% to 1% by mass of the unsaturated borate monomer, preferably 0.2% to 0.5% by mass, for example, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, etc. If the initiator is too little, effective polymerization may not be possible. If the initiator is too much, only some oligomers will be formed, and the molecular weight is not high enough, which belongs to a gel state and cannot form sufficient molecular chain entanglement with the polymer matrix, and is in a gel state. In addition, the amount of the initiator can be used to control the borate polymer to have a suitable degree of polymerization.

[0122] In principle, there is no particular restriction on the type of organic solvent, and for example, it can be selected from at least one of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

[0123] In some specific embodiments, in the mixing step, in order to achieve the migration of lithium ions, the polymer matrix and the lithium salt can be first mixed with the organic solvent and stirred thoroughly until dissolved to dissociate the lithium salt, and then the unsaturated borate monomer and the initiator are added.

[0124] In addition, the polymerization reaction may be controlled by, for example, irradiating or heating the polymerization reaction.

[0125] In some specific embodiments, the polymerization reaction may be caused by heating when a thermal initiator is used. There is no particular limitation on the reaction temperature, and the desired reaction temperature may be used according to the type of initiator. For example, when azobisisobutyronitrile is used, the temperature may be in the range of 60-80°C. In some preferred embodiments, the reaction temperature may be 40 to 80°C, such as 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, etc.; the reaction time may be 4 to 18 hours, such as 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, etc.

[0126] In some more specific embodiments, the reaction can be carried out under an inert gas condition such as argon. Specifically, an inert gas can be introduced into the mixed solution after the mixing step to expel the air dissolved in the solvent and in the reaction container, and then the mixture is sealed.

[0127] In other specific embodiments, free radicals can be formed and polymerization of monomers can be initiated by ultraviolet light irradiation when a photoinitiator is used. The polymerization reaction time can be several minutes. The advantages of photoinitiated polymerization are fast polymerization speed, less solvent volatilization, environmental friendliness, low cost, low energy consumption, etc.

[0128] In some specific embodiments, the manufacturing method further includes a film forming step, and the film forming method may be a solution coating method, an extrusion casting method, or the like, which may be appropriately selected according to the purpose.

[0129] In some more specific embodiments, the solution coating method includes applying the solution to a substrate and drying it, removing the substrate, thereby obtaining a film-like polymer solid electrolyte. For the substrate, for example, it can be a glass substrate, a ceramic substrate, a stainless steel substrate, a plastic substrate, etc. For the drying temperature and time, for example, it can be dried in a vacuum drying oven at 50 to 100°C, preferably 60 to 80°C for 4 to 10 hours, preferably 4 to 8 hours. After drying, a thin film on the substrate can be obtained. Peeling the film off the substrate (i.e. removing the substrate) can obtain a film-like polymer solid electrolyte. In addition, the obtained film-like polymer solid electrolyte can also be cut into a suitable shape and size as needed, for example, it can be cut into a circular electrolyte sheet of Φ16mm.

[0130] The manufacturing method of the present invention has many advantages such as low cost, simple method, environmental friendliness, high safety of the obtained polymer solid electrolyte, and excellent cycle stability and battery capacity of the lithium ion secondary battery, and has extremely broad prospects in practical application.

[0131] Example

[0132] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0133] Example 1

[0134] (1) Preparation of polymer solid electrolyte solution:

[0135] Dissolve 4 g of polyvinylidene fluoride (PVDF), 4 g of lithium bis(trifluoromethanesulfonyl)imide (equivalent to 50% of the total mass of all polymers after polymerization) and 0.02 g of azobisisobutyronitrile (AIBN) in 30 ml of dimethylformamide (DMF), stir magnetically until dissolved, add 4 g of triallyl borate, continue mixing for 30 min, and heat and stir at 75 °C for 4 h.

[0136] (2) Preparation of composite solid polymer electrolyte membrane:

[0137] The mixed solution prepared above was poured onto a clean glass plate and dried in a vacuum drying oven at 80°C for 8 hours using a solution coating method. The film was then peeled off the glass plate and cut into a Φ16 mm circular electrolyte sheet.

[0138] The performance test of the polymer solid electrolyte sheet prepared as above was carried out to obtain the ionic conductivity, lithium ion migration number and cycle stability, as shown in Table 1.

[0139] Example 2

[0140] The difference from Example 1 is that triallyl borate is replaced by allyl boric acid pinacol ester, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests, as shown in Table 1.

[0141] Example 3

[0142] The difference from Example 1 is that PVDF is replaced by polyurethane PU, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests, as shown in Table 1.

[0143] Example 4

[0144] The difference from Example 1 is that PVDF is replaced by polyethylene oxide PEO, and the solvent DMF is replaced by dimethylacetamide DMAC. The remaining steps are the same as those in Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.

[0145] Example 5

[0146] The difference from Example 1 is that the amount of triallyl borate added is 2 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared and then subjected to subsequent performance tests. The details are shown in Table 1.

[0147] Example 6

[0148] The difference from Example 1 is that the amount of triallyl borate added is 3 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.

[0149] Example 7

[0150] The difference from Example 1 is that the amount of triallyl borate added is 5 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests. The details are shown in Table 1.

[0151] Example 8

[0152] The difference from Example 1 is that the amount of triallyl borate added is 6 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared and then subjected to subsequent performance tests. The details are shown in Table 1.

[0153] Comparative Example 1

[0154] The difference from Example 1 is that the mixed solution is not heated, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance tests, as shown in Table 1.

[0155] Comparative Example 2

[0156] The difference from Example 1 is that no unsaturated borate monomer is added, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance testing.

[0157] Comparative Example 3

[0158] The difference from Example 1 is that the unsaturated monomer added is methyl methacrylate, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared for subsequent performance testing.

[0159] <Performance Evaluation>

[0160] The polymer solid electrolyte membrane obtained in the above embodiments and comparative examples was used, and the following positive electrode preparation method was adopted: NCM (811) positive electrode material, super P, PVDF, and LiTFSI were dissolved in NMP solvent according to a mass ratio of 8:1:0.8:0.2, mixed evenly, coated on a metal aluminum foil, dried, and cut into a positive electrode sheet with a diameter of 14 mm. In addition, a metal lithium negative electrode was used as the negative electrode, which was cut into a disc with a diameter of 16 mm as the negative electrode of the button battery. The 2032 button battery was assembled in an argon glove box. The cycle stability of the battery was tested at room temperature.

[0161] At an ambient temperature of 23°C, the ionic conductivity of the solid electrolyte membrane was tested.

[0162] The calculation formula of lithium ion conductivity (S / cm) is: σ = d / RS. Where d is the thickness of the polymer solid electrolyte membrane (cm), R is the bulk impedance of the polymer solid electrolyte (Ω), and S is the effective area of ​​the polymer solid electrolyte (cm 2 ).

[0163] The polymer film was placed between two stainless steel sheets and tested using an electrochemical workstation.

[0164] The test results are shown in Table 1 below.

[0165] Table 1

[0166]

[0167] As can be seen from Table 1, in Examples 1 to 8, since borate polymers were obtained, the ion conductivity and capacity retention rate of the solid electrolytes obtained were excellent, while in Comparative Example 1, since only monomers were added and no polymers were obtained, an independently supported membrane could not be obtained, and in Comparative Example 2, since no borate polymers were added, the conductivity and capacity retention rate of the solid electrolytes obtained were very low.

[0168] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0169] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A diaphragm-free lithium-ion secondary battery, comprising a positive electrode, a negative electrode and a polymer solid electrolyte, characterized in that: The polymer solid electrolyte comprises: a borate polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C); Wherein, the borate polymer comprises a structural unit derived from an unsaturated borate monomer represented by formula (1); in, R1 to R3 are the same or different; and R1 to R3 are independently selected from monovalent organic groups, or R1 and R2 as organic groups can be connected to form a ring by bonding; at least one of R1 to R3 or the cyclic structure formed by R1 and R2 has an unsaturated structure; n represents 0 or 1, The borate ester polymer is in-situ polymerized in the polymer solid electrolyte.

2. A lithium ion secondary battery with a diaphragm, which is a lithium ion secondary battery with a diaphragm comprising a positive electrode, a negative electrode, a diaphragm and a polymer solid electrolyte, characterized in that: The polymer solid electrolyte comprises: a borate polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C); Wherein, the borate polymer comprises a structural unit derived from an unsaturated borate monomer represented by formula (1); in, R1 to R3 are the same or different; and R1 to R3 are independently selected from monovalent organic groups, or R1 and R2 as organic groups can be connected to form a ring by bonding; at least one of R1 to R3 or the cyclic structure formed by R1 and R2 has an unsaturated structure; n represents 0 or 1, The borate ester polymer is in-situ polymerized in the polymer solid electrolyte.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The unsaturated borate ester monomer has 1 to 3 unsaturated groups; Preferably, the unsaturated group is selected from alkenyl groups; more preferably, the unsaturated group is selected from alkenyl groups having 2 to 4 carbon atoms.

4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The n=1, and the R1 to R3 are independently selected from substituted or unsubstituted hydrocarbon groups having 1 to 20 carbon atoms.

5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The n=0, the R1 to R3 are independently selected from substituted or unsubstituted hydrocarbon groups having 1 to 20 carbon atoms, and R1 and R2 are connected to form a ring or are independent of each other.

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The R1 to R3 are independently selected from a linear, branched, aliphatic or aromatic hydrocarbon group having 2 to 10 carbon atoms, and the hydrocarbon group may have a substituent.

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The unsaturated borate monomer represented by formula (1) comprises at least one selected from the following: Triallyl borate, allyl borate pinacol ester, trans-crotonyl borate pinacol ester, (3-buten-1-yl) borate pinacol ester, 3-methyl-2-butenyl borate pinacol ester.

8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The mass ratio of the monomer amount of the component (A) to the monomer amount of the component (B) is 1:10 to 10:

1.

9. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The component (A) and the component (B) in the polymer solid electrolyte form an interpenetrating network structure in terms of molecular structure.

10. The lithium ion secondary battery according to any one of claims 1 to 9, characterized in that: The polymer solid electrolyte is an all-solid electrolyte.

11. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The polymer matrix is ​​selected from at least one of PVDF, PVDF-HFP, PEO and PAN.

12. The lithium ion secondary battery according to any one of claims 1 to 11, characterized in that: The mass content of the lithium salt in the polymer solid electrolyte is 10% to 60%.

13. A method for manufacturing a lithium ion secondary battery according to any one of claims 1 to 12, characterized in that: The following steps are involved: The polymer matrix, lithium salt, unsaturated borate monomer and initiator are mixed in an organic solvent to obtain a mixed solution; The unsaturated borate monomer is polymerized to obtain the polymer solid electrolyte.

Citation Information

Patent Citations

  • Polymer solid electrolyte, preparation method thereof and battery

    CN118630308A